JTGG 2018
DOI: 10.20517/jtgg.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics of medulloblastoma: imaging surrogates of molecular biology

Abstract: Medulloblastoma is a heterogeneous disease comprising four molecular subgroups-wingless (WNT), sonic hedge hog (SHH), group 3, and group 4, with distinct developmental origins, unique transcriptional profiles, diverse phenotypes, and varying clinical outcomes. Magnetic resonance imaging (MRI) is the preferred first-line imaging modality in the diagnosis and staging of suspected brain tumors including medulloblastoma. It is being increasingly recognized that imaging features reflect underlying disease biology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The special in this case is the lack of contrast enhancement ("mismatching" pattern) of the leptomeningeal metastases on the MRI. Similar examples have been found in the literature, where it is demonstrated, that the absorption of the contrast depends on the genetic type and the histological variant of the meduloblastoma cells [28,30,31]. This fact increases the significance of the MRI, not only for the diagnosis and staging of meduloblastoma, but also for the preliminary determination of the prognosis, closely related to the complex treatment.…”
Section: Discussion Of the Characteristics Of The Presented Clinical supporting
confidence: 78%
See 1 more Smart Citation
“…The special in this case is the lack of contrast enhancement ("mismatching" pattern) of the leptomeningeal metastases on the MRI. Similar examples have been found in the literature, where it is demonstrated, that the absorption of the contrast depends on the genetic type and the histological variant of the meduloblastoma cells [28,30,31]. This fact increases the significance of the MRI, not only for the diagnosis and staging of meduloblastoma, but also for the preliminary determination of the prognosis, closely related to the complex treatment.…”
Section: Discussion Of the Characteristics Of The Presented Clinical supporting
confidence: 78%
“…Mеduloblastoma (MB) is a malignant embryonal tumour, a subtype of primitive neuroectodermal brain tumors (PNET), predominantly growing infratentorially in the cerebellum [21]. MB is a heterogeneous disease comprising four molecular subgroups -wingless (WNT), sonic hedge hog (SHH), group 3, and group 4, with distinct developmental origins, unique transcriptional profiles, diverse phenotypes and varying clinical outcomes [24,25,28,29]. Some MR images of LMD in medulloblastoma appear to be characteristic, perhaps even specific to certain molecular subgroups [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the era of molecular genetics, radiogenomics have provided sufficient data to define certain molecular subtypes noninvasively, although it is quite clear that no single imaging feature is pathognomonic of any particular subgroup, certain imaging characteristics are much more prevalent in one subgroup compared to others and may even be highly specific for an individual molecular subgroup. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…In adult diffuse gliomas, contrast-enhancement has been an imaging surrogate for histologic grading, with higher grade gliomas showing signi cantly more enhancement, suggesting blood-brain barrier disruption, increased neovascularization, and transendothelial diffusion [22]. Previous studies have shown differential pattern of contrast-uptake within individual subgroups of medulloblastoma; WNT-pathway tumors are associated with bright homogenous enhancement while Group 4 medulloblastomas have large non-enhancing areas or faint/patchy contrast-uptake [12,15]. We found contrast-uptake in ≤80% of tumor volume to be associated with worse outcomes for the entire cohort and within Group 3 medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similar prediction accuracy was later reported using radiomics-based approaches with support machine vector classi er [13] and random forest model [14] to identify molecular subgroups. Several other studies have used semantic, radiomic, or spectroscopic features to predict molecular subgroups with acceptable accuracy [15,16], but none of them have attempted to correlate speci c imaging features with survival in medulloblastoma. In the present study, we report the prognostic impact of semantic MRI features on recurrence and survival in our institutional cohort of medulloblastoma across molecular subgroups as well as within individual molecular subgroups.…”
Section: Introductionmentioning
confidence: 99%